2021
DOI: 10.3389/fcell.2021.685379
|View full text |Cite
|
Sign up to set email alerts
|

An Aging-Related Gene Signature-Based Model for Risk Stratification and Prognosis Prediction in Lung Adenocarcinoma

Abstract: Aging is an inevitable time-dependent process associated with a gradual decline in many physiological functions. Importantly, some studies have supported that aging may be involved in the development of lung adenocarcinoma (LUAD). However, no studies have described an aging-related gene (ARG)-based prognosis signature for LUAD. Accordingly, in this study, we analyzed ARG expression data from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO). After LASSO and Cox regression analyses, a six ARG-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 39 publications
(37 reference statements)
0
35
0
Order By: Relevance
“…10,17 Aging can also promote carcinogenesis, tumor development and metastasis, 13,14,[17][18][19] and is a significant risk factor for colorectal tumor and lung carcinoma. 20,21 Therefore, novel aging-related markers can potentially be used to predict cancer prognosis, 33 so it is vital to understand the association between signature of aging and BC. In this study, our nomogram presented good calibration and discrimination in the TCGA set.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,17 Aging can also promote carcinogenesis, tumor development and metastasis, 13,14,[17][18][19] and is a significant risk factor for colorectal tumor and lung carcinoma. 20,21 Therefore, novel aging-related markers can potentially be used to predict cancer prognosis, 33 so it is vital to understand the association between signature of aging and BC. In this study, our nomogram presented good calibration and discrimination in the TCGA set.…”
Section: Discussionmentioning
confidence: 99%
“…13,14,[17][18][19] Identifying key characteristics and induction of senescence in tumor cells has been a recent focus of cancer research, 13 as researchers have explored and confirmed their potential diagnostic or prognostic value as biomarkers in malignancy, including colorectal and lung cancer. 10,20,21 However, its prognostic value in BC remains unknown as no precise clinical signature has been established.…”
Section: Introductionmentioning
confidence: 99%
“…Regulation of tumor cellular senescence by ARGs can inhibit tumors, but ARGs can potentially promote tumor initiation, development, and metastasis ( Johnson et al, 2013 ; Mosteiro et al, 2016 ; Galluzzi et al, 2018 ; Calcinotto et al, 2019 ; Lee and Schmitt, 2019 ). Lately, the potential diagnostic or prognostic value of ARGs have been explored and confirmed in colorectal cancer and LUAD ( Xu and Chen, 2021 ; Yue et al, 2021 ). But its prognostic values and potential mechanisms in LUSC remain unknown, and no precise ARG-based risk signature has been developed for LUSC patients.…”
Section: Introductionmentioning
confidence: 99%
“…With increasing convenience in data collection from open-access public databases, many studies concentrated on the relationship between RNA-seq data of specific gene sets and individual patient outcomes ( Wu et al, 2019 ; Qu et al, 2020 ; Zhu et al, 2020 ; Xu and Chen, 2021 ). These studies were limited to autophagy, aging, and immune infiltration, but most of them lack clinical applications.…”
Section: Discussionmentioning
confidence: 99%